Applying Cognitive Conflict Strategy to Develop Mathematical Critical Thinking Ability and Character of Students - Luh Putu Arya Putri Adnyani (JME (Journal of Mathematics Education), 2020)
This study aims to design a valid, effective, and practical learning trajectory with a cognitive conflict strategy in developing critical thinking ability and character of students on set topic learning. In learning, counter-information and guided question were given to guide the students to manage built conflict. This research is a three-stage design study with the following steps: initial preparation and design, real field implementation, and retrospective analysis. Data on student's critical thinking skills were collected through student's works in worksheets, post-test results, and interviews. As for the character of the students were seen from the observations during the learning activities. The collected data are analyzed descriptive-qualitatively. The learning trajectory of this design study had the following characteristics: The students are observing and relating the problem with their prior understanding or information they got from the sources. Students are directed to comparing and writing arguments from the counter information given to choose the correct answer. The students are realizing or finding the correct information and construct their comprehension or understanding. The students are giving conclusions and finding their method to solve the problems.